Myocoptid mites (Acariformes: Myocoptidae) of the fauna of the former USSR - Bochkov, Andre V (Zootaxa, 2016)
Mites of the family Myocoptidae (Acariformes: Sarcoptoidea) of the former USSR are revised based on the collection of the Zoological Institute RAS (St. Petersburg, Russia). Seventeen described species are recorded. Four species are described as new for science: Trichoecius dubininae sp. nov. from Lasiopodomys gregalis (Pallas) (Rodentia: Cricetidae) from Russia (Chelyabinsk Prov., type locality), Kazakhstan and Kirghizia, T. lemmus sp. nov. from Lemmus sibiricus (Kerr) (Rodentia: Cricetidae) from Russia (Taymyr peninsula), T. meriones sp. nov. from Meriones meridianus (Pallas) (Rodentia: Muridae) from Turkmenia, and Myocoptes meriones sp. nov. from Meriones tamariscinus (type host) from Kirghizia (type locality) and Meriones libycus (Lichtenstein) from Tajikistan. In addition, the presence of 7 more species in the fauna of the former USSR is considered highly probable. Myocoptids of the former USSR represent all 6 genera currently recognized in the family. Keys to species, their hosts and localities are provided and all data are summarized in tabular format. A new name Apocalyptoides nom. nov. is proposed for the preoccupied generic name Apocalypsis Bochkov, 2010 not Butler (1876).